1993
DOI: 10.21236/ada266319
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Polymorphism and Genetic Variability of One Colonized and Several Field Populations of Phlebotomus papatasi (Diptera: Psychodidae)

Abstract: The Alexandria laboratory colony and five field populations of Phlebotomus papatasi (Scopoli) from Egypt were analyzed for genetic variation at 17 enzyme loci. The laboratory colony was characterized by a low level of genetic variation as measured by the average number ofalleles per loctus i(A = 1.70 t 0. 16) and the average expected heterozygositv dfie = 0.06 t 0.02). Polymorphismn was observed at 23.5% of the examined loci, and genotype frequencies at tawo loci P(PGM. AK-2) were tound to deviate slightly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
10
0
Order By: Relevance
“…Therefore, genetic differences were expected between widely separated P. papatasi populations. Previous experiments carried by Kassem et al (1993) and Ghosh et al (1999), using isoenzyme electrophoresis of sandflies from Egypt and the Jordan Valley, documented the presence of polymorphisms at 14 of 25 loci in Egyptian strains and seven of 20 loci in the Jordan Valley strains.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, genetic differences were expected between widely separated P. papatasi populations. Previous experiments carried by Kassem et al (1993) and Ghosh et al (1999), using isoenzyme electrophoresis of sandflies from Egypt and the Jordan Valley, documented the presence of polymorphisms at 14 of 25 loci in Egyptian strains and seven of 20 loci in the Jordan Valley strains.…”
Section: Discussionmentioning
confidence: 95%
“…A variety of methods have been employed in the past to evaluate spatial components of genetic diversity among P. papatasi populations. Genomic allele frequency estimates have been used to calculate genetic diversity using allozyme (Kassem et al , 1990, 1993), mtDNA (Parvizi et al , 2003) and microsatellite loci (Hamarsheh et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They found polymorphism at 14/25 loci in P. papatasi . Kassem et al . (1993) extended their study to field populations of P. papatasi in Egypt and found no diagnostic alleles or significant gene frequency differences among five field populations and a laboratory strain, although they noted that 4–7 loci in each population deviated from the Hardy–Weinberg equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…The geographical distribution of P. papatasi includes different climatic and ecological discontinuities, where insecticide usage varies greatly, and may set different selection patterns that are favourable to local adaptation among geographically distant P. papatasi populations and are associated with patterns of population divergence (Pener & Wilamovsky, 1987; Dhiman & Mittal, 2000). When different genetic markers were used to study genetic variation in P. papatasi , such as c ytochrome b (Esseghir et al , 1997; Parvizi et al , 2003; Hamarsheh et al , 2007a), internal transcribed spacer 2 (ITS2) (Depaquit et al , 2000, 2008; Hamarsheh et al , 2007b) and isoenzyme electrophoresis (Kassem et al , 1993; Ghosh et al , 1999), it was concluded that widely separated populations of P. papatasi were genetically quite homogenous.…”
Section: Introductionmentioning
confidence: 99%